NF-κB Activation Is Involved in Regulation of Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) by Interleukin-1β - Cafferata, Eduardo Gustavo Alfredo (2001)
Interleukin-1 beta (IL-1b) regulates the levels of cystic fibrosis transmembrane conductance regulator (CFTR) mRNA and protein in the T84 human carcinoma cell line. Here, we studied the role of the transcription factor NF-kB in this regulation. Initially, T84 cells were pretreated with the NF-kB inhibitor pyrrolidine dithiocarbamate. Cells were then stimulated with IL-1b, and CFTR mRNA levels were determined after 4 h by Northern blot analysis. As a result of PDTC treatment, IL-1b stimulation of CFTR mRNA was blocked. On the other hand, daunorubicin, an NF-kB activator, increased the steady-state levels of CFTR mRNA. Furthermore, after treatment with IL-1b for 1 h, cytoplasmic IkBa degradation occurred simultaneously with translocation of p65 into the nucleus. The T84 cells were also transduced with an adenoviral vector expressing a dominant negative form of IkBa, which prevents IkBa phosphorylation and the subsequent nuclear translocation of NF-kB. After viral transduction, the cells were stimulated with IL-1b for 4 h, and CFTR mRNA levels were measured by Northern blot analysis. The stimulation of CFTR, induced by IL-1b, was also blocked in the presence of the dominant negative mutant. These results indicate that NF-kB is involved in the pathway by which IL-1b regulates CFTR.